Acute Kidney Injury After Esophageal Cancer Surgery: Incidence, Risk Factors, and Impact on Oncologic Outcomes. Issue 5 (24th May 2022) - Murphy, Conor F.; Dunne, Talulla; Elliott, Jessie A.; Kamarajah, Sivesh K.; Leighton, James; Evans, Richard P. T.; Bundred, James; King, Sinead; Ravi, Narayanasamy; Donohoe, Claire L.; Griffin, S. Michael; Griffiths, Ewen A.; et al.
Abstract : Objective: To determine the incidence, risk factors, and consequences of AKI in patients undergoing surgery for esophageal cancer Summary of Background Data: Esophageal cancer surgery is an exemplar of major operative trauma, with well-defined risks of respiratory, cardiac, anastomotic, and septic complications. However, there is a paucity of literature regarding AKI. Methods: consecutive patients undergoing curative-intent surgery for esophageal cancer from 2011 to 2017 in 3 high-volume centers were studied. AKI was defined according to the AKI Network criteria. AKI occurred if, within 48 hours postoperatively, serum creatinine rose by 50% or by 0.3 mg/dL (26.5 μmol/L) from preoperative baseline. Complications were recorded prospectively. Multivariable logistic regression determined factors independently predictive of AKI. Results: A total of 1135 patients (24.7%:75.3% female:male, with a mean age of 64, a baseline BMI of 27 kg m −2, and dyslipidemia in 10.2%), underwent esophageal cancer surgery, 85% having an open thoracotomy. Overall in-hospital mortality was 2.1%. Postoperative AKI was observed in 208 (18.3%) patients, with AKI Network 1, 2, and 3 in 173 (15.2%), 28 (2.5%), and 7 (0.6%), respectively. Of these, 70.3% experienced improved renal function within 48 hours. Preoperative factors independently predictive of AKI were age [ P = 0.027, odds ratio (OR) 1.02 (1.00–1.04)], male sex [ P = 0.015, OR 1.77 (1.10–2.81)], BMI at diagnosis [ P < 0.001, OR 1.10 (1.07–1.14)], and dyslipidemia [ P = 0.002, OR 2.14 (1.34–3.44)]. Postoperatively, AKI was associated with atrial fibrillation ( P = 0.013) and pneumonia ( P = 0.005). Postoperative AKI did not impact survival outcomes. Conclusion: AKI is common but mostly self-limiting after esophageal cancer surgery. It is associated with age, male sex, increased BMI, dyslipidemia, and postoperative morbidity.